Sistem Informasi Layanan Puskesmas Berbasis Web - Farica Perdana Putri; Florentina Kurniasari (Ultimatics : Jurnal Teknik Informatika, 2019)
Puskesmas must always improve their quality so that the services provided are faster and more effective. One of the efforts in improving the quality is the construction of information systems regarding types of services, programs, operating hours, and availability of inpatient rooms. Puskesmas Keranggan is one of the Puskesmas where the use of inpatient rooms is still done manually, without a system, so that medical personnel in different health services find it difficult to know the exact number of rooms that are still available. Therefore, Puskesmas Keranggan built a web-based information system that can be accessed quickly and easily using internet. The information system was built using the Laravel framework, Bootstrap, and MySQL. The web application is ready to use and has been built in accordance with the requirements.